THE USE OF WEB-BASED EXAM (WBE) TO OPTIMIZE STUDENTS’ TESTING RESULT - Abdul Ngafif (University of Kuningan, 2018)
This research was conducted based on theproblems found during the mid and final test by using paper and pen test; those are the students tend to do cheating, the sleepy supervisors, the inconsistency of test time, and the risk of losing the answer sheet. Therefore, the goals of the research are; 1) to make an appropriate WBE testing system, 2) to know the cheating rate of the students, 3) to find out the effectiveness of the system, and 4) to inform the benefits that might be taken by the WBE testing system’s users. By applyingRnD research model, the researcher applies a concept called web-based exam system which uses three main tools to run the system (teacher’s laptop as the server, WBE software, and access point to communicate the server and the user). The results indicated that the system reduces the students’ cheating rate 100%. Then, from the questionnaire given, the teacherstend to likeusing WBE testing system because they can monitor the whole process of the test from his own laptop and the result of the test will be analyzed and be saved automatically in his laptop. Moreover, it reduces time consumption and paper use.Keywords: web-based exam, testing system, testing result, cheating, software